2014
DOI: 10.3171/2013.9.jns122074
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell–derived factor-1 promoted angiogenesis and inflammatory cell infiltration in aneurysm walls

Abstract: Object A small percentage of cerebral aneurysms rupture, but when they do, the effects are devastating. Current management of unruptured aneurysms consist of surgery, endovascular treatment, or watchful waiting. If the biology of how aneurysms grow and rupture were better known, a novel drug could be developed to prevent unruptured aneurysms from rupturing. Ruptured cerebral aneurysms are characterized by inflammation-mediated wall remodeling. We studied the role of stromal cell-derived factor-1 (SDF-1) in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 55 publications
1
47
0
2
Order By: Relevance
“…In various studies, it could be demonstrated, that aneurysm rupture and growth are mediated by angiogenesis, infl ammatory cell infi ltration (23,24) or extracellular matrix degeneration (25) in the aneurysmal wall. Further, immunohistochemical analyses revealed differences in structural protein and vascular growth factor expressions in normal artery, as well as unruptured and ruptured aneurysm walls (26).…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, it could be demonstrated, that aneurysm rupture and growth are mediated by angiogenesis, infl ammatory cell infi ltration (23,24) or extracellular matrix degeneration (25) in the aneurysmal wall. Further, immunohistochemical analyses revealed differences in structural protein and vascular growth factor expressions in normal artery, as well as unruptured and ruptured aneurysm walls (26).…”
Section: Discussionmentioning
confidence: 99%
“…Study findings also showed SDF-1 to promote endothelial cell migration, endothelial cell tube formation (angiogenesis), and macrophage migration. [16] Inhibition of SDF-1 in the murine model significantly decreased the amount of endothelial cells and capillaries in the aneurysm wall, and the overall rate of aneurysm formation was reduced. [16] …”
Section: Pathogenesismentioning
confidence: 93%
“…[16] Inhibition of SDF-1 in the murine model significantly decreased the amount of endothelial cells and capillaries in the aneurysm wall, and the overall rate of aneurysm formation was reduced. [16] …”
Section: Pathogenesismentioning
confidence: 93%
See 2 more Smart Citations